Acute Abdomen due to Mutual Tangle of Two Small Paratubal Cysts - Hiroharu Kobayashi; Shinichi Shibuya; Kentaro Iga; Keiichiro Kato; Airi Kato; Shuhei Terada; Hiroshi Adachi (Case Reports in Obstetrics and Gynecology)
A 30-year-old woman (gravida 0) visited our hospital with a complaint of right lower abdominal pain. Transvaginal ultrasonography revealed a 5-cm swollen right ovary, which was suspected to be a mature cystic teratoma. Pelvic examination revealed moderate pain. Contrast-enhanced computed tomography showed a 44-mm cystic mass containing fat and calcified material in the right pelvis. Since torsion was suspected, emergent laparoscopic surgery was performed. Intraoperative findings were a swollen right ovary without torsion or congestion. Two small pedunculated 1- and 2-cm diameter paratubal cysts that grew from almost the same place of the ampulla of the right fallopian tube were observed. The thin stalk of the 1-cm paratubal cyst was entangled around the stalk of the 2-cm paratubal cyst, with its head congested. Through a small abdominal laparoscopic incision, the tumor of the right ovary and the two paratubal cysts were excised. Histopathological examination revealed that the right ovarian tumor was a mature cystic teratoma, and the two paratubal cysts had no malignancy. This case showed that only a 2-cm tumor with congestion caused the acute abdomen.